Induction of Macrophage M2b/c Polarization by Adipose Tissue-Derived Mesenchymal Stem Cells - Meng Sun; Linxiao Sun; Chongchu Huang; Bi-cheng Chen; Zhenxu Zhou (Journal of Immunology Research)
Background. Adipose-derived mesenchymal stem cells (ADMSCs) can promote healing and inhibit inflammation/immune response in local tissues, while the detailed mechanism remains unknown. Results. ADMSCs and peritoneal macrophages were collected from C57BL/6 mice. The culture medium (CM) from ADMSCs (24 hours cultured) was collected. The CM was added to the Mφ culture system with lipopolysaccharide (LPS) or IL-4/IL-13 or blank. And those Mφ cultures without adding CM were used as controls. A series of classification markers and signaling pathways for Mφ polarization were detected by using flow cytometry, RT-PCR, and western blotting. Furthermore, the cell viability of all the groups was detected by CCK8 assay. After CM induction in different groups, M1-Mφ markers and M2a-Mφ were decreased; however, M2b/c-Mφ markers increased. STAT3/SOCS3 and STAT6/IRF4 were suppressed in all 3 CM-treated groups. Moreover, the cell viability of all 3 groups which were induced by CM significantly increased as compared to that of the control groups without adding CM. Conclusion. ADMSCs can induce nonactivated macrophage and M1-Mφ into M2b/c-Mφ. Downregulation of the STAT3 and STAT6 pathway may involve in this process. This data shows that the anti-inflammatory role of ADMSC in local tissues may be partly due to their effect on Mφ to M2b/c-Mφ.